Measuring Faith with Numbers: Can Islamic Religious Education Exams Assess Spiritual Understanding? - Andriani, Anita; Al Ayyubi, Ibnu Imam; Apriyanti, Niken Siti Nur; Nurhikmah; Rahmawati, Siti (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2025)
This study aims to evaluate whether numerical results from IRE exams can accurately reflect students' overall spiritual comprehension. Through both quantitative and qualitative analysis, the study finds that relying solely on test scores is insufficient to assess students’ faith and spiritual insight. Significant differences in learning outcomes between schools suggest that variations in teaching methods and assessment systems contribute to these disparities. Interviews with students and teachers reveal that IRE exams, which tend to emphasize memorization, fall short in uncovering deeper understanding of religious values. In contrast, assessment approaches that are more relevant to everyday life, encourage reflection, utilize narrative methods, and observe student behavior are perceived as more effective. Therefore, an ideal model for assessing Islamic Religious Education should integrate both cognitive evaluation and spiritual reflection through a comprehensive, holistic approach. By combining written assessments with contextual inquiry, personal reflection, and behavioral observation, educators can gain a more accurate and authentic picture of students’ religious understanding. Such a multifaceted evaluation system not only enhances the relevance of PAI but also supports the formation of students who genuinely embody Islamic values in their daily lives.